The Effect of Tax Planning, Profitability, and Capital Structure on Corporate Income Tax Liabilities with Operating Costs as A Moderating Variable - Evelyne Shafina; Indra Pahala; Etty Gurendrawati (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
This research examines how tax planning, profitability, and capital structure influence corporate income tax, with operating costs playing a moderating role. The analysis centers on publicly traded manufacturing firms listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023. Employing secondary data from audited statements and purposive sampling, the research analyzes 284 firm-year observations from 71 companies. The key variables are operationalized as follows: ETR for tax planning, ROA for profitability, DER for capital structure, and total SG&A expenses for operating costs. Analysis using a panel data Fixed Effects Model (FEM) with Moderated Regression Analysis (MRA) in EViews 13 reveals a positive and significant impact of profitability on tax obligations, with no significant effects found for tax planning or capital structure. Furthermore, operating costs strengthen the positive relationship between profitability and tax. Conversely, operating costs negatively and significantly moderate the effects of both tax planning and capital structure on corporate income tax. These findings highlight the critical role of operating cost efficiency in shaping how financial factors influence tax obligations. The study contributes to academic taxation literature and offers practical insights for firms in developing compliant tax strategies.